PENDIDIKAN KARAKTER DI PERGURUAN TINGGI DALAM PEMBANGUNAN DI ERA MEA - Joko Mursitho (Ri'ayah: Jurnal Sosial dan Keagamaan, 2016)
The experience model approach, social media, and individual approach called success when; firstly, the lecturers have ability to present their material more variative and interesting because it is integrated with character, through the implementation of inquiry model, social model, and individual model. In applying the Tri Darma’s values of University the lecturers can set the material better. Secondly, exciting presentations are able to decrease the discrepancy relationship among lecturers and learners. Thirdly, lecturers can make contact with other better institutions both profit and non profit to make link between campus and employment which are the real life in society.